Penerapan Etika Bisnis Islam dalam Perdagangan Bawang Merah di Pasar Sukomoro Nganjuk - Agus Tohawi; Juni Iswanto; Subekan Subekan; Dewi Fitrtotus Sa`Diyah; Mastur Mastur (Journal on Education, 2023)
This research focuses on the practice of buying and selling Red Onions in the Sukomoro Market, Nganjuk Regency, and the application of Islamic business ethics principles by traders. Prophet Muhammad, as a trader, provides a historical context. The research method employed is qualitative with a descriptive approach. Primary data is obtained from wholesale Red Onion traders, retail traders, and buyers; while secondary data comes from observations and archives. The findings indicate that transaction practices generally adhere to Islamic principles such as honesty and avoidance of deception. However, there is still a lack of understanding in the principles of trustworthiness and fair competition. In the application of Islamic business ethics, some traders do not fully comprehend the principles of accountability and tauhid. Nevertheless, the principles of justice, freedom, and ihsan have been well applied in trade. The research aims to understand and enhance traders' understanding of Islamic business ethics.